2020
DOI: 10.1002/pmrj.12324
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Home‐Based Respiratory Muscle Training from the Perspectives of Individuals Who Had a Stroke: Qualitative Study

Abstract: Background: Although the significance of respiratory muscle training has been established in the literature, there is a need to understand the participantsʼ perceptions of the benefits of this intervention. Objective: To understand how individuals who had a stroke perceive changes in their body functions and structures, activities, and participation after a high-intensity respiratory muscle training intervention and to understand their perceptions of the benefits and limitations of a home-based intervention. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Recently, much attention has been paid to respiratory training, which has achieved the goal of improving lung function of patients through exercises such as glottic vocalization training and breathing exercise. Some scholars believe [ 5 ] that performing respiratory training for COPD patients is able to effectively improve their respiratory function, thus resulting in improved pulmonary function, and this training modality has been demonstrated in patients with cancer complicated by stroke, stroke hemiparesis, and chronic rotator cuff injury [ 6 8 ]. Western medicine can effectively improve many discomfort symptoms in patients, and it plays an important role in anti-inflammation and improving diaphragm function.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much attention has been paid to respiratory training, which has achieved the goal of improving lung function of patients through exercises such as glottic vocalization training and breathing exercise. Some scholars believe [ 5 ] that performing respiratory training for COPD patients is able to effectively improve their respiratory function, thus resulting in improved pulmonary function, and this training modality has been demonstrated in patients with cancer complicated by stroke, stroke hemiparesis, and chronic rotator cuff injury [ 6 8 ]. Western medicine can effectively improve many discomfort symptoms in patients, and it plays an important role in anti-inflammation and improving diaphragm function.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies have demonstrated that individuals who have survived stroke report positive perceptions of remote- 10 or semi-supervised home-based interventions. 11 Benefits included observed improvements in body structures and functions, emotional well-being, and the convenience of conducting sessions at home. These perceptions have been corroborated by physiotherapists and patients with varied health conditions, who consulted via videoconference during the Covid-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…These perceptions have been corroborated by physiotherapists and patients with varied health conditions, who consulted via videoconference during the Covid-19 pandemic. 12 However, home-based interventions require more commitment to training, 11 and their effects should be similar or superior to those provided by centre-based interventions, in order to be implemented.…”
Section: Introductionmentioning
confidence: 99%